Tailoring of Vibration Test Specifications for a Flight Vehicle - Kumar, Manoj; Rao, T. Narasirnha; Jagadisan, K.; Rao, K. Jayathirtha (Defence Science Journal, 2002)
Most equipment are subjected to vibration environment during their useful life. It is seen that nearly half of the failures observed during the flights of. satellite launch vehicles or missiles are due to mechanical vibration and shock. Thus, these stresses must be carefully considered while defining the specifications. Specifications are established for a system for use during a simulation test to show that a product meets the requirements concerning resistance to the environment. If the equipment operates smoothly during a test, there should be a very strong probability that it will perform its intended task correctly in the real environment and vice versa. Hence, the specification must be at least as severe as the real environment and also representative of the real environment. It is also required that no other item of the equipment built according to the same design should fail in operation. Specifications should take care of this and thus the envelop of data obtained during the real world environment should be considered. Generally at the design stage and the initial development stage, existing standards like the Military Specifications or Joint Service Specifications are used as guidelines for formulating the specifications. This causes either an overtest or an undertest with regards to the overall spectrum or in specific frequency bands for any given structure. To overcome this, it is essential to develop a correct specification using the telemetry data acquired for a few flights and a method is required to be formulated for deriving the specifications out of the telemetry data so obtained. This paper discusses the formulation of a specification methodology, and algorithm in general. The above method is applied to a series of flight data obtained for a particular flight vehicle to derive a specification representative of the real world environmental conditions (tailoring).